Species Differences in Paraoxonase Mediated Hydrolysis of Several Organophosphorus Insecticide Metabolites - Russell L. Carr; Mary Beth Dail; Howard W. Chambers; Janice E. Chambers (Journal of Toxicology)
Paraoxonase (PON1) is a calcium dependent enzyme that is capable of hydrolyzing organophosphate anticholinesterases. PON1 activity is present in most mammals and previous research established that PON1 activity differs depending on the species. These studies mainly used the organophosphate substrate paraoxon, the active metabolite of the insecticide parathion. Using serum PON1 from different mammalian species, we compared the hydrolysis of paraoxon with the hydrolysis of the active metabolites (oxons) of two additional organophosphorus insecticides, methyl parathion and chlorpyrifos. Paraoxon hydrolysis was greater than that of methyl paraoxon, but the level of activity between species displayed a similar pattern. Regardless of the species tested, the hydrolysis of chlorpyrifos-oxon was significantly greater than that of paraoxon or methyl paraoxon. These data indicate that chlorpyrifos-oxon is a better substrate for PON1 regardless of the species. The pattern of species differences in PON1 activity varied with the change in substrate to chlorpyrifos-oxon from paraoxon or methyl paraoxon. For example, the sex difference observed here and reported elsewhere in the literature for rat PON1 hydrolysis of paraoxon was not present when chlorpyrifos-oxon was the substrate.